Evaluasi Kebijakan Pengelolaan Pasar Tradisional di Pasar Baru Kefamenanu Kabupaten Timor Tengah Utara - Sherly Dewitry Nenobota; Fidelis Atanus; Yohanes Fritantus (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The formulation of the research problem is what are the results of traditional market management policies in Pasar Baru Kefamenanu, North Central Timor Regency. The aim of this research is to analyze and describe the Traditional Market Management Policy at Pasar Baru Kefamenanu, North Central Timor Regency. This research uses qualitative methods to describe the management of traditional markets in Pasar Baru Kefamenanu, North Central Timor Regency. Data collection techniques through observation, interviews and documentation. The results of this research show that the Traditional Market Management Policy in Pasar Baru Kefamenanu, North Central Timor Regency has been implemented well in accordance with time and costs; The adequacy and maintenance of supporting facilities and infrastructure for markets in the form of stalls, public toilets and parking areas, still needs to be optimized by the relevant agencies; the provision of buildings/places provided has not been fully utilized by the traders because the buildings/places built are ineffective or not in accordance with the wishes of the traders; Responsiveness in the Management of Traditional Markets at Pasar Baru Kefamenanu, North Central Timor Regency regarding the responses or responses of traders and consumers in the management of Pasar Baru Kefamenanu is positive and does not cause problems;  The government has taken steps to improve management at the Kefamenanu New Market as well as possible, but traders and consumers still need to improve.